PENGARUH ETIKA KERJA DAN PENGALAMAN KERJA TERHADAP PRESTASI KERJA PEGAWAI PADA KANTOR SEKRETARIAT DPRD KOTA SIBOLGA - Christamara Simanjuntak; Kaharuddin; Rosmita Ambarita (JURNAL EKONOMI BISNIS DAN MANAJEMEN, 2023)
The formulation of the problem in this study is whether work ethics and work experience simultaneously influence the work performance of employees at the Sibolga City DPRD Secretariat Office? The purpose of this study is to find out and analyze whether there is an effect of work ethics and work experience on employee performance at the Sibolga City DPRD Secretariat Office. The hypothesis of this study is that there is an effect of work experience on employee performance at the Sibolga City DPRD Secretariat Office. The population is 108 people and the sample is 52 people. The results showed that work ethics and work experience simultaneously affect employee performance, where Fcount (86.578) is greater than Ftable (3.18) and Sig.á (0.000b) is smaller than α 5% (0.005). There is an influence of work ethics on employee performance, where the tcount value of 5.511 is greater than the ttable value of 2.008 or a significant (Sig-t) of 0.000 less than α (0.05). There is the influence of work experience on employee performance, where the tcount value of 2.780 is greater than the ttable value of 2.008 or a significant (Sig-t) of 0.008 less than α (0.05). 77.9% work ethics and work experience can affect employee performance. The positive sign in the multiple linear regression equation, namely Y = 4.825 + 0.552X1 + 0.314X2 indicates that employee performance will increase if work ethics and work experience are good.